Multi-stage diarization refinement for the CHiME-7 DASR scenario - Boeddeker, Christoph; Cord-Landwehr, Tobias; von Neumann, Thilo; Haeb-Umbach, Reinhold (7th International Workshop on Speech Processing in Everyday Environments (CHiME 2023))

Mixture Encoder for Joint Speech Separation and Recognition - Berger, Simon; Vieting, Peter; Boeddeker, Christoph; Schlüter, Ralf; Haeb-Umbach, Reinhold (INTERSPEECH 2023)

Analysis of polycarbonate degradation at melt/FeCr-alloy interfaces as a function of the alloy composition by means of combinatorial thin film chemistry - Theile-Rasche, Chantal; Meng, T.; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (SN Applied Sciences)
Interfacial reactions at the polycarbonate (PC)/FeCr-alloy interface during melt contact were studied as function of the Fe:Cr ratio within the alloy. Thin Fe/Cr films with lateral composition gradients were deposited by magnetron sputtering; the analysis of the films was done with microscopy and X-ray photoelectron spectroscopy (XPS). The local interfacial polymeric film formation could be therefore directly correlated with the Fe:Cr ratio. The local thickness and structure of the formed polycarbonate residue was analyzed by means of imaging ellipsometry, atomic force microscopy as well as Fourier-transform infrared spectroscopy under grazing incidence and XPS. Moreover, confocal fluorescence microscopy of the PC melt/alloy interface could reveal the formation of minor degradation products in the interphase region. The results show that already an Fe:Cr ratio of 2 : 1 leads to a strong inhibition of the thermal degradation in comparison to the unalloyed iron, and that in general, the enrichment of chromium in the passive film leads to an effective suppression of interfacial PC degradation. The data contributes to improving the mechanistic understanding of the role of iron during this process. Additionally, a critical concentration of chromium in the alloys used for PC processing can be deduced.

PECVD and PEALD on polymer substrates (part II): Understanding and tuning of barrier and membrane properties of thin films - de los Arcos de Pedro, Maria Teresa; Awakowicz, Peter; Böke, Marc; Boysen, Nils; Brinkmann, Ralf Peter; Dahlmann, Rainer; Devi, Anjana; Eremin, Denis; Franke, Jonas; Gergs, Tobias; Jenderny, Jonathan; Kemaneci, Efe; et al. (PLASMA PROCESSES AND POLYMERS)
Plasma Processes and Polymers is a plasma journal focusing on the interdisciplinary field of low temperature plasma science.

PECVD and PEALD on polymer substrates (part I): Fundamentals and analysis of plasma activation and thin film growth - de los Arcos de Pedro, Maria Teresa; Awakowicz, Peter; Benedikt, Jan; Biskup, Beatrix; Böke, Marc; Boysen, Nils; Buschhaus, Rahel; Dahlmann, Rainer; Devi, Anjana; Gergs, Tobias; Jenderny, Jonathan; von Keudell, Achim; et al. (PLASMA PROCESSES AND POLYMERS)

Complementary spectroscopic and electrochemical analysis of the sealing of micropores in hexamethyldisilazane plasma polymer films by Al 2 O 3 atomic layer deposition - Xie, Xiaofan; Zanders, David; Preischel, Florian; de los Arcos de Pedro, Maria Teresa; Devi, Anjana; Grundmeier, Guido (Surface and Interface Analysis)

Das Lesen von Fachtexten in der beruflichen Schule der Migrationsgesellschaft. Ein aktuelles Thema für den Deutschunterricht oder auch alle anderen Fächer? - Dehn, Freya (Berufsbildender Deutschunterricht im Kontext von Migration und Einwanderung)

A Sub-Threshold Microwave RFID Tag Chip, Compatible With RFID MIMO Reader Technology - Haddadian, Sanaz; Scheytt, J. Christoph; von Bögel, Gerd; Grenter, Thorben (IEEE Journal of Radio Frequency Identification)
We present a fully integrated radio frequency identifications transponder chip operating at 5.8 GHz, which is compatible with the class-1 generation-2 of the Electronic Product Code protocol (EPC-C1 G2). The tag chip including the analog front-end and the digital baseband processor, are designed in the sub-threshold regime (0.5 V) with a total supply current of less than 50 μA. As a power scavenging unit, a single-stage differential-drive rectifier structure is designed and fabricated with standard threshold voltage (SVT) MOS elements in a commercial 65-nm CMOS process, to provide 0.8 V of rectified voltage. Measurements performed on the fabricated single-stage structure show a maximum power conversion efficiency of 69.6% for a 22 kΩ load and a sensitivity of -12.5 dBm, which corresponds to more than 1 m of reading range. The power conversion efficiency at this range is about 64%.

Business Models for Cultural Event Platforms - A Taxonomy Approach - Althaus, Maike; Grieger, Nicole; Vorbohle, Christian; Müller, Michelle; Kundisch, Dennis (Proceedings of the 15th Mediterranean Conference on Information Systems (MCIS))

Entwurf eines einstufigen Ladewandlers auf Basis eines LLC-Resonanzwandlers - Keuck, Lukas
Heutige On-Board-Ladewandler sind typischerweise aus zwei Stufen aufgebaut, die über einen Spannungszwischenkreis verbunden sind. Als erste Stufe kommt ein PFC-Gleichrichter zum Einsatz, der die Anforderungen an den Netzstrom bezüglich Oberschwingungsgehalt und Leistungsfaktor sicherstellt. Für die zweite Wandler-Stufe hat sich in den vergangenen Jahren ein LLC-Resonanzwandler qualifiziert, der die Ladeleistung an die Traktionsbatterie galvanisch getrennt überträgt. Der Zwischenkreis besteht aus einer Bank von Elektrolytkondensatoren, in denen die pulsierende Eingangsleistung zwischengespeichert wird. Die Kondensatoren machen einen erheblichen Teil des Lader-Volumens aus und altern schnell, was insbesondere für Ladewandler an Bord von Elektrofahrzeugen unerwünscht ist. In der vorliegenden Arbeit wird untersucht, ob diese zweistufige Struktur verworfen werden kann, indem der LLC-Resonanzwandler direkt an die gleichgerichtete Netzspannung angeschlossen wird.Zum Einsatz des LLC-Resonanzwandlers als einstufiger Ladewandler ist die Schaltung für einen großen Strom- und Spannungsbereich auszulegen. Hierfür wird in der vorliegenden Arbeit eine erweiterte Zeitbereichsanalyse erarbeitet, deren hohe Modellierungsgenauigkeit im Anschluss experimentell nachgewiesen wird. Mit Hilfe dieser Zeitbereichsanalyse werden die Belastungsgrößen des Resonanzwandlers berechnet, um hiermit eine Vorauswahl der Schaltungsparameter treffen zu können. Darauf aufbauend erfolgt die Optimierung des integrierten Transformators als Schlüsselkomponente des Ladewandlers sowie dessen prototypische Realisierung. Abschließend wird mittels Prototypen die erzielbare Leistungsdichte ermittelt. Ergebnis: Verglichen mit etablierten Ladewandlern der heutigen Elektrofahrzeuge konnte durch den einstufigen Ansatz die Leistungsdichte um ca. 53% gesteigert werden.

Neurocognitive Errors and Noncontact Anterior Cruciate Ligament Injuries in Professional Male Soccer Players - Gokeler, Alli; Tosarelli, Filippo; Buckthorpe, Matthew; Della Villa, Francesco (Journal of Athletic Training)
Context Evidence is emerging that core neurocognitive functions such as working memory and inhibitory control (ie, motor-response and attentional inhibition) are linked to the anterior cruciate ligament (ACL) injury risk. Research has been conducted in laboratory settings, but the contribution of neurocognition to actual ACL injuries under real-world conditions is unknown. Objective To describe the possible neurocognitive errors involved in noncontact ACL injury mechanisms. Design Case series. Setting Soccer matches. Patients or Other Participants A total of 47 professional male soccer players. Main Outcome Measure(s) Three independent reviewers evaluated 47 videos of players sustaining noncontact ACL injuries. Neurocognitive errors in inhibitory control were operationalized as follows: (1) motor-response inhibition was scored when a player demonstrated poor decision-making and approached the opponent with high speed that reduced the ability to stop or change the intended action and (2) an attentional error was scored when a player shifted his selective attention away from the relevant task to irrelevant stimuli. Results Of 47 noncontact ACL injuries, 26 (55%) were related to a pressing-type injury, 19 (73%) of which involved a deceiving action made by the opponent, suggesting poor inhibitory control of the defender. Of the remaining 21 noncontact ACL injuries (45%), 16 (76%) could be attributed to attentional errors. Agreement among the 3 raters was very good for all items except poor decision-making, which showed fair to good agreement (Fleiss κ = 0.71). Interrater reliability was excellent (intraclass correlation coefficient = 0.99–1.00). Conclusions Errors in motor-response inhibitory control and attentional inhibition were common during noncontact ACL injury events in professional male soccer players. The interrater agreement in detecting neurocognitive errors in general was very good.

Relationships Between Task Constraints, Visual Constraints, Joint Coordination and Football-Specific Performance in Talented Youth Athletes: An Ecological Dynamics Approach - Heuvelmans, Pieter; Di Paolo, Stefano; Benjaminse, Anne; Bragonzoni, Laura; Gokeler, Alli (Perceptual and Motor Skills)
Individual performance in team sports is a multifactorial reflection of how well a player can cope and accomplish tasks in varied playing situations. Thus, performance analysis should not only focus on outcomes, but also on underlying mechanisms of those outcomes. We adopted principles of the ecological dynamics approach (EDA) to investigate the effect of introducing constraints on players’ joint coordination responses for a football-specific performance drill outcome. Seventeen talented youth football (soccer) players performed a football-specific drill under different conditions: basic constraints, additional defender dummies, stroboscopic glasses, and a combination of the latter two constraints. We recorded these players’ execution time, passing accuracy, and lower extremity joint kinematics. We calculated joint coordination for hip-knee, knee-ankle, and trunk-hip couplings. The added constraints negatively affected execution time and passing accuracy, and caused changes in joint coordination. Furthermore, we identified a relationship between execution time and joint coordination. This study serves as an example how the EDA can be adopted to investigate mechanisms that underlie individual performance in team sports.

Comparing the Effects of Differential and Visuo-Motor Training on Functional Performance, Biomechanical, and Psychological Factors in Athletes after ACL Reconstruction: A Randomized Controlled Trial - Gholami, Fatemeh; Letafatkar, Amir; Moghadas Tabrizi, Yousef; Gokeler, Alli; Rossettini, Giacomo; Ghanati, Hadi Abbaszadeh; Schöllhorn, Wolfgang Immanuel (Journal of Clinical Medicine)
Variation during practice is widely accepted to be advantageous for motor learning and is, therefore, a valuable strategy to effectively reduce high-risk landing mechanics and prevent primary anterior cruciate ligament (ACL) injury. Few attempts have examined the specific effects of variable training in athletes who have undergone ACL reconstruction. Thereby, it is still unclear to what extent the variations in different sensor areas lead to different effects. Accordingly, we compared the effects of versatile movement variations (DL) with variations of movements with emphasis on disrupting visual information (VMT) in athletes who had undergone ACL reconstruction. Forty-five interceptive sports athletes after ACL reconstruction were randomly allocated to a DL group (n = 15), VT group (n = 15), or control group (n = 15). The primary outcome was functional performance (Triple Hop Test). The secondary outcomes included dynamic balance (Star Excursion Balance Test (SEBT)), biomechanics during single-leg drop-landing task hip flexion (HF), knee flexion (KF), ankle dorsiflexion (AD), knee valgus (KV), and vertical ground reaction force (VGRF), and kinesiophobia (Tampa Scale of Kinesiophobia (TSK)) assessed before and after the 8 weeks of interventions. Data were analyzed by means of 3 × 2 repeated measures ANOVA followed by post hoc comparison (Bonferroni) at the significance level of p ≤ 0.05. Significant group × time interaction effects, main effect of time, and main effect of group were found for the triple hop test and all eight directions, SEBT, HF, KF, AD, KV, VGRF, and TSK. There was no significant main effect of group in the HF and triple hop test. Additionally, significant differences in the triple hop test and the seven directions of SEBT, HF, KF, KV, VGRF, and TSK were found between the control group and the DL and VMT groups. Between group differences in AD and the medial direction of SEBT were not significant. Additionally, there were no significant differences between VMT and the control group in the triple hop test and HF variables. Both motor learning (DL and VMT) programs improved outcomes in patients after ACL reconstruction. The findings suggest that DL and VMT training programs lead to comparable improvements in rehabilitation.

Conclusion-based Counter-Argument Generation - Alshomary, Milad; Wachsmuth, Henning (Proceedings of the 17th Conference of the European Chapter of the Association for Computational Linguistics)
In real-world debates, the most common way to counter an argument is to reason against its main point, that is, its conclusion. Existing work on the automatic generation of natural language counter-arguments does not address the relation to the conclusion, possibly because many arguments leave their conclusion implicit. In this paper, we hypothesize that the key to effective counter-argument generation is to explicitly model the argument‘s conclusion and to ensure that the stance of the generated counter is opposite to that conclusion. In particular, we propose a multitask approach that jointly learns to generate both the conclusion and the counter of an input argument. The approach employs a stance-based ranking component that selects the counter from a diverse set of generated candidates whose stance best opposes the generated conclusion. In both automatic and manual evaluation, we provide evidence that our approach generates more relevant and stance-adhering counters than strong baselines.

Concurrent validation of the Xsens IMU system of lower-body kinematics in jump-landing and change-of-direction tasks - Nijmeijer, Eline M.; Heuvelmans, Pieter; Bolt, Ruben; Gokeler, Alli; Otten, Egbert; Benjaminse, Anne (Journal of Biomechanics)

Hermann Lotze’s Influence on the Twentieth Century Philosophy - Milkov, Nikolay

Bertrand Russell’s Philosophical Logic and its Logical Forms - Milkov, Nikolay (Athens Journal of Philosophy)
From 1901 to 1919, Russell persistently maintained that there were two kinds of logic and distinguished between one and the other as mathematical logic and philosophical logic. In this paper, we discuss the concept of philosophical logic, as used by Russell. This was only a tentative program that Russell did not clarify in detail; therefore, our task will be to make it explicit. We shall show that there are three (-and-a-half) kinds of Russellian philosophical logic: (i) “pure logic”; (ii) philosophical logic investigating the logical forms of propositions; (iii) philosophical logic exploring the logical forms of facts: in epistemology and in the external world. In particular, Russell’s program or philosophical logic of the facts of the external world remained less than sketchily outlined.
Keywords: Russell; mathematical logic; philosophical logic; Wittgenstein

Calibration of Large Coherent MIMO Radar Arrays: Channel Imbalances and 3D Antenna Positions - Greiff, Christian; Mateos-Núñez, David; Simoni, Renato; González-Huici, Maria; Kruse, Stephan; Scheytt, J. Christoph; Kolk, Karl; Höller, Christian; Kurz, Heiko Gustav; Meinecke, Marc-Michael; Gisder, Thomas (2023 24th International Radar Symposium (IRS))
One of the main challenges for next generation automotive radars is the improvement of angular resolution to a sub-degree level. In this context, wide aperture automotive radars of 1m length or more and resolution close to 0.1° in azimuth and 0.5° in elevation could be beneficial. To enable coherent processing of arrays with such large aperture, prior (i.e offline) and online calibration are necessary: channel imbalances (gains and phases) and three dimensional coordinates of transmit and receive elements need to be determined. We propose a calibration strategy based on alternating steps between the two subtasks of i) channel imbalance estimation with ‘known’ array positions, by applying a singular value decomposition to the resulting tensor calculus problem; and ii) antenna position estimation with ’known’ channel imbalances, by numerically maximizing the Bayesian posterior probability; in both cases operating on range/Doppler snapshots of disjoint targets (with potentially unknown locations). Simulation studies based on the parameters of a MIMO 8x6 linear sparse array show promising results as long as the initial position errors do not exceed half a wavelength (2mm), beyond which we observe strong effects of ambiguity. Experimental results with real measurements show that after calibration in laboratory conditions, our MIMO 8x6 demonstrator with 50cm aperture is able to resolve two targets at the same range with angular separation at least as close as 0.4°.

Distributed System Architecture for Software-Defined Radio / Radar with Optical Signal Distribution - Kruse, Stephan; Kneuper, Pascal; Schwabe, Tobias; Meinecke, Marc-Michael; Kurz, Heiko G.; Scheytt, J. Christoph
In this paper we present a new system architecture for software-defined radio / radar with optical signal distribution. The proposed architecture allows to transmit the optical carrier and an arbitrary IQ signal on the same fiber from a base station to wireless transmitters using a single laser. Furthermore, we can reuse parts, and under special conditions, also the complete optical output of the base station for the IQ return path from the wireless receiver frontends to the base station. Avoiding multiple lasers and fibers for the distribution of the carrier and arbitrary signal from the base station to the frontend, and avoiding the laser diode for the IQ return path from receiver frontends to the base station reduces the hardware effort significantly. Finally, the system architecture allows to integrate all components of the optoelectronic wireless frontend in a single chip using silicon photonics technology.

Analysis and Simulation of a Coherent FMCW Lidar-Photonic Radar Combined Sensor System for Large Aperture Phased Array MIMO - Kruse, Stephan; Meinecke, Marc-Michael; Kneuper, Pascal; Schwabe, Tobias; Kurz, Heiko G.; Scheytt, J. Christoph (2023 20th European Radar Conference (EuRAD))